High tumor expression of CTLA4 identifies lymph node-negative basal-like breast cancer patients with excellent prognosis - Røssevold, Andreas Hagen; Tekpli, Xavier; Lingjærde, Ole Christian; Russnes, Hege G.; Vallon-Christersson, Johan ; 0000-0002-2195-0385; Borgen, Elin; Lømo, Jon; Garred, Øystein; Dorraji, Esmaeil; Kristensen, Vessela N.; Naume, Bjørn; Kyte, Jon Amund (Communications medicine, 2025)
Background: Tumor immune cell infiltration is a favorable prognostic factor in triple-negative breast cancer. Most triple-negative tumors belong to the aggressive basal-like subtype. We hypothesized that immune gene expression may identify low-risk patients for whom adjuvant chemotherapy can be de-escalated. Methods: The expression of 753 immune-related genes was analyzed in tumor biopsies from 45 patients with basal-like disease and no lymph node metastases (Oslo1 cohort) and evaluated for prognostic value. Findings were validated in two independent cohorts. Oslo1 biopsies were also analyzed for tumor-infiltrating lymphocytes (TIL) and tertiary lymphoid structures (TLS). Results: Here we show that a high expression of CTLA4 (above 63rd percentile) is associated with an excellent prognosis in the Oslo1 cohort. None of the patients in the CTLA4high group suffered disease recurrence (median follow-up 7.4 years) or breast cancer-related death (median follow-up 17.7 years). Analysis of the SCAN-B (n = 233; 97% without distant recurrence in CTLA4high group) and METABRIC cohorts (n = 155; 93% disease-specific survival in CTLA4high group) validates this finding, which also applies to patients who did not receive chemotherapy. CTLA4 expression correlates with TIL score and TLS levels (Oslo1 cohort), but no TILlow/CTLA4high patients died from breast cancer, suggesting that the CTLA4 readout identifies low-risk patients not captured by TIL assessment. Conclusions: A high primary tumor expression of CTLA4 identifies patients with an excellent prognosis, for whom standard chemotherapy may be de-escalated or omitted.